Engineered nanomaterials trigger abscopal effect in immunotherapy of metastatic cancers - Xia, Yuanliang; Yang, Ruohan; Zhu, Jianshu; Wang, Hengyi; Li, Yuehong; Fan, Jiawei; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Despite advances in cancer treatment, metastatic cancer is still the main cause of death in cancer patients. At present, the treatment of metastatic cancer is limited to palliative care. The abscopal effect is a rare phenomenon in which shrinkage of metastatic tumors occurs simultaneously with the shrinkage of a tumor receiving localized treatment, such as local radiotherapy or immunotherapy. Immunotherapy shows promise for cancer treatment, but it can also lead to consequences such as low responsiveness and immune-related adverse events. As a promising target-based approach, intravenous or intratumoral injection of nanomaterials provides new opportunities for improving cancer immunotherapy. Chemically modified nanomaterials may be able to trigger the abscopal effect by regulating immune cells. The aim of this review is to discuss the application of nanomaterials in killing metastatic tumor cells through the regulation of immune cells and its prospects for clinical adoption.